1973
DOI: 10.1029/wr009i004p01047
|View full text |Cite
|
Sign up to set email alerts
|

Clogging in simulated glacial aquifers due to artificial recharge

Abstract: Clogging due to artificial recharge in laboratory-simulated unconsolidated aquifers displayed two types of patterns. The first type, resulting from recharge with turbid water containing an effective microbial inhibitor, showed clogging throughout the aquifers ranging in length from 48 to 123 cm. The rate of clogging at different depths was dependent on the size distribution of the particles in the water relative to the pore size distribution of the porous media. Clogging tended to be more severe at the infiuen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

1978
1978
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…It has adverse effects in various field applications that rely on the use of water injection wells or on the development of biologically active zones (BAZs). Examples of these applications are the artificial recharge of groundwater [Avnimelech and Nevo, 1964;Ripley and Saleem, 1973;Wood and Bassett, 1975;Oberdorfer and Peterson, 1985], the disposal of wastewater [Mitchell and Nevo, 1964;Laak, 1970;Davis et al, 1973;Chang et al, 1974], groundwater extraction [van Beek and van der Kooij, 1982;van Beek, 1984] or, in recent years, the in situ bioremediation of contaminated aquifer sediments [Lee et al, 1988].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has adverse effects in various field applications that rely on the use of water injection wells or on the development of biologically active zones (BAZs). Examples of these applications are the artificial recharge of groundwater [Avnimelech and Nevo, 1964;Ripley and Saleem, 1973;Wood and Bassett, 1975;Oberdorfer and Peterson, 1985], the disposal of wastewater [Mitchell and Nevo, 1964;Laak, 1970;Davis et al, 1973;Chang et al, 1974], groundwater extraction [van Beek and van der Kooij, 1982;van Beek, 1984] or, in recent years, the in situ bioremediation of contaminated aquifer sediments [Lee et al, 1988].…”
Section: Introductionmentioning
confidence: 99%
“…As simple as this two-compartment structure may seem, the extreme variety of organisms involved, as well as the large number of mechanisms that appear responsible for the clogging process, makes the development of such a mathematical model a very daunting task. Indeed, aside from bacteria [e.g., Calaway, 1957;Mitchell and Nevo, 1964;Laak, 1970;van Beek, 1984;Shaw et al, 1985], there is evidence that fungi [Ripley and Saleem, 1973;Okubo and Matsumoto, 1983] and protozoa [Hilton and Whitehall, 1979;Okubo and Matsumoto, 1983] are also associated with the clogging process. Various mechanisms have been invoked in the literature to account for the microbial clogging of porous media.…”
Section: Introductionmentioning
confidence: 99%
“…For example, K s reduction was found to be associated with the production of N 2 (Ronen et al, 1989;Tollner et al, 1983;Wood andBassett, 1975) andCH 4 (De Lozada et al, 1994;Reynolds et al, 1992). Some experiments have shown that FeS precipitates (Davis, 1967;Van Beek, 1984) and other organisms, such as fungi (Okubo and Matsumoto, 1983;Ragusa et al, 1994;Ripley and Saleem, 1973;Seki et al, 1996) and protozoans (DeLeo and Baveye, 1997;Mattison et al, 2002;Okubo and Matsumoto, 1983), can be observed in clogged porous materials. However, their effects, especially in the case of protozoans, are still somewhat poorly understood.…”
Section: Introductionmentioning
confidence: 90%
“…Several researchers (e.g. Rebhun & Schwarz, 1968;Behnke, 1969;Ripley & Saleem, 1973;Wood & Bassett, 1975;Vigneswaran & Suazo, 1987;Warner et al 1994) reported the accumulation of suspended particulate matter that causes the progressive clogging of the soil in the ponds or trenches used for aquifer recharge. When the recharging water contains suspended solids of a size commensurate with that of the particles of the porous medium, suspended solids penetration does not occur to any significant extent, and accumulation at the surface leads to the formation of a filter cake, which reduces the overall hydraulic conductivity of the medium as reported by Baveye et al (1998).…”
Section: Discussionmentioning
confidence: 99%